Effect of light of different intensity on chlorophyll fluorescence of Ulva pertusa Kjellman (Chlorophyta) - Posudin, Yu.; Mitsunobu Kamiya; Akio Murakami; Hiroshi Kawai (Альгология, 2005)
The effects of high-intensity optical radiation on chlorophyll fluorescence of marine alga Ulva pertusa Kjellman (Chlorophyta) were investigated. Method of pulse amplitude modulated (PAM) chlorophyll fluorescence was used for studying the photoinhibition of photosynthesis of alga.